Editorial - Phupong, Vorapong (Thai Journal of Obstetrics and Gynaecology, 2023)
This third issue of Thai Journal of Obstetrics and Gynaecology (TJOG) 2023 contains many interesting articles. One special article is “Marijuana in Obstetric Patients”. The detail of article includes scientific knowledge about marijuana, Thai law on marijuana, and maternal and fetal effect of marijuana use during pregnancy and lactation. Editor in Chief and managing staff of TJOG already attended “the 14th Thai Journal Development Network Seminar” on Wednesday, March 15, 2023 at the Royal Jubilee Ballroom, G Floor, IMPACT Building. Challenger, Muang Thong Thani, Nonthaburi, Thailand. TCI conducts activities and a project to continuously improve the quality of Thai journals since 2004. The aims of this meeting were to improve the national policy on research and quality development of Thai journals and notify editors of the revised evaluation criteria for TCI journals whose journals are currently indexed in the TCI. Editorial Board of TJOG looks forward to continuously raising the quality of the TJOG.